Extra-follicular Variant of Adenomatoid Odontogenic Tumor: A Diagnostic Enigma - Shrestha, Sarju; Rimal, Jyotsna; Maharjan, Iccha Kumar; Regmee, Pragya; Luitel, Abhinaya; Jaisani, Mehul Rajesh; Paswan, Chandrakant; Shrestha, Ashish (Journal of BP Koirala Institute of Health Sciences, 2022)
Adenomatoid odontogenic tumor (AOT) is an uncommon, slow-growing, noninvasive odontogenic tumor mostly in the anterior maxilla with three well-recognized clinico-pathological variants: follicular, extra-follicular, and peripheral. Extra-follicular variant presents as a well-defined, unilocular, radiolucency in between, above, or superimposed on the roots of an erupted tooth. A 19 years female reported with the chief complaint of a loose tooth in the right front region of the upper jaw for 6 months, associated with firm swelling without pain or discharge. On orthopantomogram and cone-beam computed tomography, the lesion appeared as a single, localized, well-defined, roughly oval unilocular radiolucency with flecks of radiopacity integrating radicular and cervical third of 13. Complete surgical enucleation followed by histopathological examination revealed the lesion as AOT.The extra-follicular AOT can cause diagnostic dilemmas and is often misdiagnosed as an odontogenic cyst.